Multistage Off-line Permutation Packet Routing on a Mesh: an Approach with Elementary Mathematics - CHIEW, Kevin (Institutional Knowledge at Singapore Management University, 2009)
Various methods have been proposed for off-line permutation packet routing on a mesh. One of the methods is known as multistage routing, in which the first stage is crucial. For the first stage of routing, the previous study normally converts it to a problem of graph theory and proves the existence of solutions. However, there is a lack of simple algorithms to the first stage of routing. This article presents an explicit and simple approach for the first stage of routing based on elementary mathematics.